2006
DOI: 10.1002/ijc.22069
|View full text |Cite
|
Sign up to set email alerts
|

Use of tight belts and risk of esophageal adenocarcinoma

Abstract: It has recently been hypothesized that the general shift in use from suspenders to belts among men might be a factor that could promote reflux, particularly among overweight men, and thereby contribute to the alarmingly increasing incidence of esophageal and cardia adenocarcinoma. We addressed this hypothesis in a nationwide Swedish population-based case-control study, conducted in 1995-1997. Included were 189 patients with esophageal adenocarcinoma and 262 patients with cardia adenocarcinoma, who were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While a number of factors including race, obesity, use of esophageal sphincter-relaxing drugs, smoking, and alcohol consumption have all been incriminated as possible etiological factors in esophageal adenocarcinoma [34,35,36,37,38], many cohort studies have pointed strongly to gastroesophageal reflux and Barrett's disease (Barrett's esophagus) as a causative factor [39,40]. There is a strong dose-response relationship between previous gastroesophageal reflux symptoms and esophageal adenocarcinoma, but the relationship to cardia cancer is weaker [40].…”
Section: Adenocarcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of factors including race, obesity, use of esophageal sphincter-relaxing drugs, smoking, and alcohol consumption have all been incriminated as possible etiological factors in esophageal adenocarcinoma [34,35,36,37,38], many cohort studies have pointed strongly to gastroesophageal reflux and Barrett's disease (Barrett's esophagus) as a causative factor [39,40]. There is a strong dose-response relationship between previous gastroesophageal reflux symptoms and esophageal adenocarcinoma, but the relationship to cardia cancer is weaker [40].…”
Section: Adenocarcinomamentioning
confidence: 99%
“…The relationship to smoking is less clear than that for SCC. Increased abdominal pressure brought about by central obesity, sedentary posture, and tight belts has also been implicated [37,65], although a high body mass index appears to be an independent risk factor for adenocarcinoma but not SCC [38].…”
Section: Epidemiology and Clinical Presentation In Esophageal Cancermentioning
confidence: 99%
“…In modern society, the practice of wearing tight-fitting clothing to show off stylish and fashionable clothes has spread widely 1 ) . However, a number of studies have reported that when excessive pressure is exerted constantly on specific parts of the human body, it can lead to many health problems in the cardiovascular system and internal organs 1 , 2 ) . Experts have expressed a negative view on the effect of tight-fitting clothing on health 2 , 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have reported that when excessive pressure is exerted constantly on specific parts of the human body, it can lead to many health problems in the cardiovascular system and internal organs 1 , 2 ) . Experts have expressed a negative view on the effect of tight-fitting clothing on health 2 , 3 ) . Furthermore, it has been suggested that wearing a waist belt frequently for a long time, can cause back pain and that this pain is due to imbalance between forces of muscles around the abdomen and waist muscles; the authors also suggested that this should be studied in the future 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the risks associated with tight clothes. They reported that tight clothes such as tight belts, ties, and jeans, which are becoming increasingly popular, have a constraining influence on the abdomen, which in turn might promote reflux 4,5) . Recently, wearing tight skirts has become fashionable.…”
Section: Introductionmentioning
confidence: 99%